2015
DOI: 10.1159/000374063
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Spironolactone on Endothelial-to-Mesenchymal Transition in HUVECs via Notch Pathway

Abstract: Background: Fibrosis results in excessive buildup of extracellular matrix proteins along with abnormalities in structure and is partly derived by a process involving transforming growth factor β (TGF-β) called endothelial-to-mesenchymal transition (EndMT). We investigated whether the aldosterone receptor-blocker spironolactone could abrogate TGF-β-induced fibrosis in EndMT and the underlying mechanism. Methods: Human umbilical vein endothelial cells (HUVECs) were divided into 5 groups for treatment: blank; veh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…Several studies have shown that other adhesion molecules, such as VE-cadherin and PECAM-1 (CD31), can be modulated by TRPM4 [28] and TRPM7 [29]. Endothelial dysfunction is a complex and multistep process that includes endothelial cell migration [30-33]. Our data clearly demonstrate that H 2 O 2 considerably promotes EC migration and that inhibition of TRPM4 with 9-phenanthrol significantly inhibits H 2 O 2 -induced migration of HUVECs.…”
Section: Discussionsupporting
confidence: 57%
“…Several studies have shown that other adhesion molecules, such as VE-cadherin and PECAM-1 (CD31), can be modulated by TRPM4 [28] and TRPM7 [29]. Endothelial dysfunction is a complex and multistep process that includes endothelial cell migration [30-33]. Our data clearly demonstrate that H 2 O 2 considerably promotes EC migration and that inhibition of TRPM4 with 9-phenanthrol significantly inhibits H 2 O 2 -induced migration of HUVECs.…”
Section: Discussionsupporting
confidence: 57%
“…EndMT facilitates cell migration and the generation of new tissue types during development and contributes to the pathogenesis of fibrosis [52]. Endothelial cells are normally closely packed with each other, which limits their potential for migration and dissociation from the matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Supernatant protein content was quantified by the Bradford method. Samples were separated on a polyacrylamide gel and then transferred to a nitrocellulose membrane [40,41]. After blockage, the membrane was incubated with primary antibody.…”
Section: Methodsmentioning
confidence: 99%